MEMBANGUN IMAJINASI KEHIDUPAN SOSIAL MELALUI PERANCANGAN KARAKTER PENDUKUNG PROFIL MASKOT KAMPUS FSRD UNTAR - Budi Darmo; Edy Chandra (Gorga : Jurnal Seni Rupa, 2024)
Mascots in their development have become a visual identity tool for a company, for designers must know the main factors needed by users to recognize mascots (Lin et al., 1999). The form of a mascot is generally in the form of representatives in the form of animals and the like. Campus is an educational institution that is equivalent to companies that need mascot figures to build their image. Mascots are fictional figures who are able to build identity in creating and expressing the personality of the brand they represent (Ardi &; Munawarah, 2021). FSRD Untar as an educational institution that seeks to build its visual character through mascot figures in human form which are generally the hallmark of mascots of a company (Chandra, 2022). The form of the mascot designed by FSRD is only limited to the appearance of its visual profile, not yet to an interesting and more complex "storytelling". Ronald McDonald and his colleagues are one example of the success of a storytelling-based visual product campaign. Through the process of creating works that refer to the process of stages of exploration, experimentation and visualization , it becomes a reference solution for the creative process in an effort to build the visual imagination of the supporting characters of the FSRD mascot profile named "Sarang." The hope to be achieved in this design study is the creation of a social group of "Sarang" mascot figures that can liven up the atmosphere of the FSRD mascot community. The atmosphere of life will be a character that is in accordance with the character of educational products at FSRD Untar.Keywords: Visual Character, Nest, Imagination, SocialAbstrakMaskot pada pengembangannya telah menjadi alat identitas visual bagi sebuah perusahaan, bagi desainer wajib mengetahui faktor utama yang dibutuhkan pengguna untuk mengenali maskot (Lin et al., 1999). Wujud maskot pada umumnya berwujud perwakilan dalam bentuk binatang dan sejenisnya. Kampus merupakan sebuah lembaga pendidikan yang disetarakan dengan perusahaan yang membutuhkan figur maskot untuk membangun pencitraannya. Maskot merupakan figur fiksional yang mampu membangun identitas dlam menciptakan dan mengekpresikan personalitas brand yang diwakilinya (Ardi & Munawarah, 2021). FSRD Untar sebagai lembaga pendidikan yang berupaya membangun visual karakternya melalui figur maskot dalam wujud manusia yang umumnya menjadi ciri khas maskot dari sebuah perusahaan (Chandra, 2022). Wujud maskot yang di rancang oleh FSRD hanya sebatas pada kemunculan profil visualnya saja, belum sampai pada sebuah sebuah storytelling yang menarik dan lebih kompleks. Ronald McDonald dan rekan-rekannya merupakan salah satu contoh keberhasilan sebuah kampanye visual produk yang berbasis storytelling. Melalui proses metode penciptaan karya yang mengacu kepada proses tahapan eksplorasi, eksperimen dan visualisasi menjadi solusi rujukan proses kreatif dalam upaya membangun imajinasi visual karakter pendukung profil maskot FSRD yang diberi nama Sarang. Harapan yang akan dicapai dalam studi perancangan ini adalah terciptanya sebuah kelompok sosial dari figur maskot œSarang yang dapat menghidupkan suasana dari masyarakat maskot FSRD. Suasana kehidupan yang hidup akan menjadi sebuah karakter yang sesuai dengan karakter produk pendidikan di FSRD Untar.Kata Kunci: Karakter Visual, Sarang, Imajinasi, Sosial Authors:Budi Darmo : Universitas TarumanegaraEdy Chandra : Universitas Tarumanegara References:Alim, B., & Chandra, E. (n.d.). REBRANDING UMKM MENTAI MELALUI PERANCANGAN IDENTITAS VISUAL. Gorga: Jurnal Seni Rupa, 12(1), 174“181.Allison, A. (2000). A challenge to Hollywood? Japanese character goods hit the US. Japanese Studies, 20(1), 67“88.Ardi, F. P., & Munawarah, P. A. (2021). Kajian Perancangan Karakter Maskot Universitas Pendidikan Mandalika. JTIM: Jurnal Teknologi Informasi Dan Multimedia, 3(1), 46“52.Bouissou, J.-M. (2006). Japan™s growing cultural power. The example of manga in France. Leipziger UniversitÃ¤tverlag.Chandra, E. (2022). Peran Figur Maskot œSarang Sebagai Brand Personality Fsrd Untar Dimata Masyarakat Indonesia. Prosiding SENAPENMAS, 2(1), 1052“1958.Gravett, P. (2004). Manga: Sixty years of Japanese comics. (No Title).Kampfner, J. (2002). Ronald McDonald has a new friend. New Statesman, 131(4611), 14“15.Kern, A. (2020). Manga from the floating world: comicbook culture and the kibyÅshi of Edo Japan. Brill.Kern, A. L. (2007). KibyÅshi in the Harvard-Yenching Library: A Guided Tour.Kinsella, S. (2015). Adult manga: Culture and power in contemporary Japanese society. Routledge.Lin, R., Lin, P. C., & Ko, K. J. (1999). A study of cognitive human factors in mascot design. International Journal of Industrial Ergonomics, 23(1“2), 107“122. https://doi.org/https://doi.org/10.1016/S0169-8141(97)00106-6Paberz, C. (2020). Communities of Craftsmen: Reflections on Japanese Manga from South Korean Manhwaga. Mechademia, 12(2), 6“23.Patriani, S. R. (2019). Pembelajaran Menggambar Ilustrasi Gaya Realis. SNHRP, 381“389.Power, N. O. (2009). God of comics: Osamu Tezuka and the creation of post-World War II manga. Univ. Press of Mississippi.Purwatia, A. G. (2017). PENCIPTAAN KARAKTER FANTASI ILUSTRASI GRAFIS MELALUI MANGA STUDIO EX5 YANG SESUAI TIPE KEPRIBADIAN MANUSIA MENURUT ENNEAGRAM.Susanto, M. (2011). Diksi rupa: Kumpulan istilah dan gerakan seni rupa (Edisi revisi). Dicti Art Dan Djagat Art House.Takahashi, R. (2004). InuYasha Ani-Manga, Vol. 1 (1st ed.). VIZ Media LLC. https://www.goodreads.com/book/show/22715.InuYasha_Ani_Manga_Vol_1Widyokusumo, L. (2013). Fungsi Garis pada Desain dan Sketsa. Humaniora, 4(1), 339“347.